2007
DOI: 10.1002/ejoc.200600959
|View full text |Cite
|
Sign up to set email alerts
|

Glycals in Organic Synthesis: A Systematic Strategy for the Preparation of Uncommon Piperidine 1,2‐Dideoxy‐L‐azasugars and 2‐Deoxy‐1,5‐anhydro‐L‐hexitols

Abstract: A systematic synthetic strategy has been developed for producing uncommon piperidine 1,2-dideoxy-L-azasugars. This method involves the formation of open intermediates such as 2, 7, and 10 easily by ring-opening of D-glycals with aqueous mercury(II) acetate/sodium borohydride. A concise sequence of regioselective amination and cyclization reactions then allowed us to prepare the cyclic compounds 5a and 5b, L enantiomers of naturally occurring fagomine congeners such as 3-epi-fagomine (II) and 3,4-di-epi-fagomin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…The spectroscopic data for compounds 25a and 25b were in accordance with the literature data. [20] The removal of the benzyl ethers in 25a and 25b was carried out with Pd(OH) 2 in MeOH to afford fully deprotected -fagomine (5) and 4-epi--fagomine (6) in 80 % and 85 % yields, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The spectroscopic data for compounds 25a and 25b were in accordance with the literature data. [20] The removal of the benzyl ethers in 25a and 25b was carried out with Pd(OH) 2 in MeOH to afford fully deprotected -fagomine (5) and 4-epi--fagomine (6) in 80 % and 85 % yields, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…However, syntheses of fagomine isomers such as 2 and 3 have been reported much more rarely. [19f] Most synthetic efforts have been directed towards the synthesis of fagomines possessing the naturally occurring  configuration; only Shipman and co-workers were able to produce the -configured fagomine diastereomer as a by-product, [18d] whereas Passacantilli and co-workers [20] reported the synthesis of 1,2-dideoxy--azasugars from -glycal derivatives.…”
Section: Introductionmentioning
confidence: 99%
“…An initial study showed that the commonly used tosylate and mesylate leaving group at C3 of 4,6-O-benzylidene galactosides did not allow for inversion reactions to occur, which is not surprising as literature [9][10] reports inversions at furanose and open-chain carbohydrate secondary carbons but rarely on pyranose secondary carbons, why tuning the sulfonate leaving ability was required. Herein, we report an alternative synthetic route towards 3-azido-3-deoxy-β-D-galactopyranosides replacing labile triflates with more stable, but still sufficiently reactive, aryl sulfonates.…”
Section: Introductionmentioning
confidence: 99%